Relevansi Fatwa dan Yurisprudensi di Era Globalisasi (Pengaruh Globalisasi terhadap Sistem Hukum di Indonesia) - Kirom Ashofchatul Wahid, Aqmarul (Program Studi Hukum Keluarga Islam (HKI) dan bekerjasama dengan Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Pesantren Sunan Drajat Lamongan, 2024)
Fatwa and jurisprudence are two important instruments in the life of Indonesian society, especially the Muslims. Fatwa is a guideline of Islamic law issued by the scholars, while juriprudency is the result of the judges in deciding a matter. In the era of globalization, both instruments remained relevant and important to the Indonesian society. Fatwa remains relevant in the era of globalization because it is able to provide solutions to the various problems that arise in society. Fatwa can be formulated by a comprehensive method, that is, by integrating Islamic values with universal values. Thus, the fatwa can be the right guideline for Indonesian society especially the Muslims in the face of the challenges of globalization. Jurisprudence also remains relevant in the era of globalization as it can be a reference for judges in deciding a case. Jurisprudence can provide an overview of how Indonesian law is applied in real life. Thus, jurisprudence can be a source of law that adapts to changing times. The development of fatwa and jurisprudence can be done by involving various stakeholders, whether scholars, judges, the public, academics, or the public.